A Comparison of Headache Treatment in the Emergency Department: Prochlorperazine Versus Ketamine - Zitek, Tony; Gates, Melanie; Pitotti, Christopher; Bartlett, Alexandria; Patel, Jayme; Rahbar, Aryan; Forred, Wesley; Sontgerath, Joseph S.; Clark, Jill M. (Annals of emergency medicine, 2018)
Intravenous subdissociative-dose ketamine has been shown to be effective for pain management, but has not been specifically studied for headaches in the emergency department (ED). For this reason, we designed a study to compare standard treatment (prochlorperazine) with ketamine in patients with benign headaches in the ED. This study was a multicenter, double-blind, randomized, controlled trial with a convenience sample of patients presenting to the ED with benign headaches. Patients were randomized to receive either prochlorperazine and diphenhydramine or ketamine and ondansetron. Patients' headache severity was measured on a 100-mm visual analog scale (VAS) at 0, 15, 30, 45, and 60 minutes. Nausea, vomiting, anxiety, and the need for rescue medications were also tracked. Patients were contacted at 24 to 48 hours posttreatment to rate their satisfaction and to determine whether they were still experiencing a headache. There were a total of 54 subjects enrolled. Two patients in the ketamine group and one in the prochlorperazine group withdrew because of adverse effects of the medications. In regard to the primary outcome, at 60 minutes, the prochlorperazine group had a mean improvement in VAS pain scores of 63.5 mm compared with 43.5 mm in the ketamine group, corresponding to a between-groups difference of 20.0 mm (95% confidence interval [CI] 2.8 to 37.2 mm) and a P value of .026. At 45 minutes, the prochlorperazine group had a mean improvement in pain scores of 56.1 mm compared with 38.0 mm in the ketamine group, a difference of 18.1 mm (95% CI 1.0 to 35.2 mm). At 24- to 48-hour follow-up, the mean satisfaction score was 8.3 of 10 for prochlorperazine and 4.9 of 10 for ketamine, a difference of 3.4 (95% CI 1.2 to 5.6). There was not a statistically significant difference in the percentage of patients who had a headache at follow-up or in other secondary outcomes. Prochlorperazine appears to be superior to ketamine for the treatment of benign headaches in the ED.